2002
DOI: 10.1128/cdli.9.2.425-432.2002
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation in Cardiovascular and Periodontal Disease: Comparative Study

Abstract: Epidemiological studies have implicated periodontal disease (PD) as a risk factor for the development of cardiovascular disease (CVD). These studies addressed the premise that local infection may perturb the levels of systemic inflammatory mediators, thereby promoting mechanisms of atherosclerosis. Levels of inflammatory mediators in the sera of subjects with only PD, only CVD, both diseases, or neither condition were compared. Subjects were assessed for levels of C-reactive protein (CRP), serum amyloid A (SAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0
15

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(160 citation statements)
references
References 70 publications
9
131
0
15
Order By: Relevance
“…In addition, its serum concentrations remain stable under physiological conditions (Fournier et al, 2000;Hochepied et al, 2003).A comparison of the healthy samples versus the diseased ones showed that α-1-acid glycoprotein 1 levels were up-regulated by 2-fold in periodontitis. Higher levels of this molecule have been previously reported in the sera of subjects with periodontitis (Glurich et al, 2002).…”
Section: Identification and Quantification Of Gcf Proteinsmentioning
confidence: 81%
“…In addition, its serum concentrations remain stable under physiological conditions (Fournier et al, 2000;Hochepied et al, 2003).A comparison of the healthy samples versus the diseased ones showed that α-1-acid glycoprotein 1 levels were up-regulated by 2-fold in periodontitis. Higher levels of this molecule have been previously reported in the sera of subjects with periodontitis (Glurich et al, 2002).…”
Section: Identification and Quantification Of Gcf Proteinsmentioning
confidence: 81%
“…AAG is an acute phase reactant that is known to play an immunomodulatory role (26). In patients with chronic myelogenous leukemia in blastic phase, AAG levels reflect pharmacological resistance to chemotherapy (27).…”
Section: Discussionmentioning
confidence: 99%
“…SAA serum levels have been reported to be raised in subjects affected by periodontitis and other co-morbidities (i.e. CVD), but in individuals with periodontitis only (Glurich et al 2002). Vuletic et al (2008) showed that 3 months after full-mouth extraction, serum levels of SAA were statistically significant lower when compared to pre-treatment (Appendix S5).…”
Section: Acute-phase Proteinsmentioning
confidence: 99%